(untitled) (Medical Forum Monthly, 2020)
Objective: This project aimed at selecting the least corrosive mouthwash that can be prescribed by working practitioners during the orthodontic treatment when their patient is being treated with Stainless Steel (SS) wire for longer periods. Study Design: Comparative study. Place and Duration of Study: This study was conducted at the Institute of Space Technology (IST) Islamabad. Standard medium for this study i.e., artificial saliva was prepared at the Interdisciplinary Research Centre in Biomedical Materials (IRCBM) Comsats University, Lahore from December 2018 to April 2019. Materials and Methods: A comparative study was designed between acid and fluoride-containing mouthwashes for a valuable addition in the existing literature by evaluating corrosive effects on orthodontic wires. Sample wires were properly cleaned and coated with an epoxy resin. Two types of mouthwashes were used as test solutions whereas artificial saliva was considered as a standard test solution. After testing the wires, their surface morphology was explored under a Field Emission Scanning Electron Microscope (FESEM). The numeric data were then statistically analyzed by One-Way ANOVA using the SPSS version 23.0. Results: Mouthwash containing HCl in 0.15% w/v of Benzydamine Hydrochloride showed lesser corrosion than the one having Fluoride content in 0.05% w/v of Sodium Monofluorophosphate. Conclusion: This study suggested that in clinical practice, acid-containing mouthwash should be preferred over fluoride-containing mouthwashes when SS wires are employed for longer durations during the orthodontic treatment.